Konsep Diversi Penanganan Anak Penyalahguna Narkotika dalam Sistem Peradilan Pidana Anak Indonesia untuk Masa Yang Akan Datang - Baskoro, Novi Eko (Pemuliaan Hukum, 2019)
Narcotics abuse is not only a national problem, but has become a global problem (world). Currently, narcotics abuse has entered all levels of society to the limit of gender, economic class, and even the age of the child. The Indonesian Government’s policy in handling narcotics abuse as regulated in Law Number 35 Year 2009  concerning Narcotics still positions narcotics abusers as criminal acts with the threat of criminal sanctions without differentiating the age limit of the perpetrators. Specifically for the handling of narcotics abuse children based on Law Number 11 Year 2012 concerning the Juvenile Criminal System, diversion must be sought. The existence of diversion is based on the fact that the criminal justice process against children dealing with the law through the formal criminal justice system causes more harm than good. Based on these problems, research is carried out using the normative legal research method, by taking an approach that is, the statutory approach related to diversion. The results showed that the concept of diversion which should be applied in Indonesia in the future, is not much different from the concept of diversion that is applied in Australia, namely Police Diversion. This is based on the consideration of the Police as the first gate to deal with children in conflict with the law to determine whether a child will proceed to the judicial process or other informal actions.